(untitled) (Research, Society and Development, 2021)
Lipoma is a benign tumor of mesenchymal origin with uncertain etiology. They have a predilection for men, between 50 and 70 years old and the trunk and extremities being the most common sites. Clinically, they appear as well-circumscribed lesions, mobile, soft to the touch, painless with a sessile or pedunculate base. The diagnosis is mostly clinical being confirmed through histopathological analysis and imaging exams and the treatment of choice is conservative surgical resection. The aim of this paper is to report a case of surgical treatment of an extensive lipoma in the submandibular region in a woman patient, 67 years old, who presented an increase in volume in the right submandibular region. On clinical examination, the patient presented a well-defined, mobile, soft palpation and painless lesion. An excisional biopsy was recommended. Under general anesthesia, Risdon’s submandibular incision, divulsion of subcutaneous tissues and hemostasis of bleeding vessels were performed. The surgery continued with resection of the lesion, cavity toilet and continuous intradermal suture using layers. The pathological specimen was sent to the Pathology Department of the Hospital das Clínicas, Federal University of Pernambuco which showed a lesion measuring 14cm x 6.5 cm in size with obtaining confirmation of lipoma hypothesis. The case was accompanied for six years showing good aesthetic and functional results without recurrence. Therefore, even if not very frequent in the head and neck region, the Maxillofacial Surgeon needs to know the characteristics of this type of pathology, as well as the appropriate form of treatment to prevent recurrences.